A PROSPECTIVE STUDY ON ANAEMIA AS A MORTALITY RISK FACTOR IN DIABETIC AND NON-DIABETIC PATIENTS FOLLOWING ACUTE MYOCARDIAL INFARCTION. - Bharti, Rashmi Rani; Kumar, Sanjay; Singh, Guddi Rani; Kumari, Mamta (Student's Journal of Health Research Africa, 2023)
Introduction: Short-term mortality is related to hyperglycemia, acute myocardial infarction (AMI), and anemia. Diabetes patients are more likely to suffer from anemia. To investigate the impact of diabetes patients also having anemia on myocardial infarction outcomes, we conducted a retrospective study. Methodology: From a registry that is disease-specific and population-based, information about every patient consecutively hospitalized with AMI was gathered. Diabetes and anemia were present in four groups of patients. Results: 32.2% of Group A, 16% of Group B, 21.45% of Group C, and 6.6% of Group D experienced 30-day mortality (all p < 0.001). Groups A, B, C, and D had, in that order, 31 days to 36 months mortality rates of 47.6%, 20.8%, 34.3%, and 10.4% (all p < 0.001). At 36 months, the odds ratios for diabetes and anemia were 1.61 (1.40–1.84, p < 0.001) and 1.58 (1.37–1.86, p < 0.001), respectively, suggesting that both illnesses remained independent risk factors for death. Of the deaths that occurred between 31 days and 36 months, 43.7% in Group A were due to cardiovascular causes, 54.0% in Group B, 47.1% in Group C, and 50.9% in Group D (p < 0.05, A vs. B). Conclusion: When compared to either diabetes or anemia patients alone, patients who have diabetes and anemia both have a greater death rate. In all groups, cardiovascular death continued to be the most common death cause. Recommendation: According to our findings, individuals with anemia who have experienced a myocardial infarction with or without diabetes may safely have prompt primary percutaneous coronary intervention; nevertheless, they should take extra care to maintain hemoglobin levels.